Investigating the Impact of Sustainable Supply Chain Management for Soil Conservation in Iran's Mining Sector - Mohammad Taleghani; Mohammadreza Jabreilzadeh Sola (Journal of Managerial Sciences and Studies, 2025)
This article investigates the impact of sustainable supply chain management (SSCM) practices on soil conservation within Iran's mining sector. As mining activities pose significant threats to soil health and environmental stability, implementing SSCM has emerged as a viable strategy to mitigate these effects. The study employs a mixed-methods approach, combining quantitative data from a questionnaire distributed to industry experts with qualitative insights gathered through in-depth interviews. Findings indicate that the adoption of key SSCM practices—including resource efficiency, effective waste management, and supplier collaboration—leads to measurable improvements in soil conservation outcomes. However, the study also identifies challenges such as regulatory inadequacies, financial constraints, and a lack of awareness among stakeholders that hinder effective implementation. Despite these obstacles, opportunities for advancement are present, particularly through government incentives and partnerships between mining companies and local communities. The results underscore the importance of integrating sustainable practices within the mining sector to enhance soil protection efforts. This research contributes to the broader discourse on sustainable mining practices, highlighting the need for a transition toward environmentally responsible operations that prioritize both economic and ecological sustainability.